The Game as a Teacher's Tool: Permainan sebagai Alat Pengajaran - Nuritdinovna, Mardieva Dilrabo (Indonesian Journal of Education Methods Development, 2023)
This article investigates the efficacy of utilizing business games as a pedagogical tool for teaching the Russian language. The author examines the distinctive features and adaptations of business games, advocating for their utilization in group learning settings to foster collaborative problem-solving and simulate diverse scenarios. The study aims to elucidate the goals, methods, and results associated with implementing business games in language education. Findings suggest that the collaborative nature of these games enhances group dynamics and facilitates a comprehensive approach to language learning. The implications of integrating business games into language education underscore the potential for improved engagement, problem-solving skills, and adaptability among learners. Highlights: Enhanced Engagement: Business games offer a dynamic and interactive approach to language education, fostering increased student engagement and participation. Collaborative Problem-Solving: The use of business games promotes collaborative learning environments, where students actively engage in solving common tasks, enhancing their teamwork and problem-solving skills. Simulated Real-World Scenarios: Business games simulate diverse situations, providing learners with practical and realistic language contexts, thereby preparing them for real-world language use. Keywords: Business Games, Language Education, Collaborative Learning, Pedagogical Tools, Russian Language